Prozdrowotna aktywność turystyczna w cyklu życia rodziny = Pro-health tourist activity in family life cycle - Kaiser, Alicja; Sokołowski, Marek; Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2016)
Kaiser Alicja, Sokołowski Marek, Mrozkowiak Mirosław. Prozdrowotna aktywność turystyczna w cyklu życia rodziny = Pro-health tourist activity in family life cycle. Journal of Education, Health and Sport. 2016;6(10):353-364. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162894 http://ojs.ukw.edu.pl/index.php/johs/article/view/3952 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016. PROZDROWOTNA AKTYWNOŚĆ TURYSTYCZNA W CYKLU ŻYCIA RODZINY PRO-HEALTH TOURIST ACTIVITY IN FAMILY LIFE CYCLE Alicja Kaiser1, Marek Sokołowski2, Mirosław Mrozkowiak3 1 Zakład Dydaktyczny Turystyki i Rekreacji, Wyższa Szkoła Bankowa w Poznaniu, Polska 2 Zakład Sportów Nowoczesnych i Obronnych, Akademia Wychowania Fizycznego im. Eugeniusza Piaseckiego w Poznaniu, Polska 3 Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Adres do korespondencji: Alicja Kaiser, dr nauk o kulturze fizycznej, Wyższa Szkoła Bankowa w Poznaniu, Zakład Dydaktyczny Turystyki i Rekreacji, al. Niepodległości 2, 61-874 Poznań tel. +48 600 92 99 95 e-mail: alicja_kaiser@poczta.fm Streszczenie Wprowadzenie. Zgodnie z rozwojową koncepcją rodziny, środowisko rodzinne przeobraża się, a każde stadium stanowi okres, w którym struktura i funkcjonowanie są jakościowo różne. Znajduje to odzwierciedlenie w realizacji przez rodzinę zdrowego stylu życia. Jedną z form zachowań zdrowotnych jest aktywność fizyczna, która zmienia się w ontogenezie i zależy od czynników biologicznych oraz aktualnej sytuacji społecznej i życiowej. Ważnym rodzajem aktywności fizycznej rodziny jest turystyka. Cel pracy. W związku z powyższym celem pracy jest analiza preferencji dotyczących aktywności turystycznej młodych osób o zróżnicowanej sytuacji rodzinnej w kontekście wzmacniania potencjału zdrowia rodziny. Materiały i metody. Badania empiryczne wykonano w 2015r. w grupie 200 kobiet z I i II stadium ontogenezy rodziny. Zastosowano metodę sondażu diagnostycznego, technikę ankiety z autorskim kwestionariuszem. W analizie statystycznej wykorzystano test chi2 i test dokładny Fishera. Wyniki i wnioski. Badane rodziny z I i II fazy ontogenezy różnią się w zakresie częstotliwości podróży turystycznych (p<0.01), wyboru otoczenia podczas wyjazdów wakacyjnych (p<0.05) oraz preferowanego rodzaju wyżywienia (p<0.01). Podobieństwa dostrzega się natomiast w zakresie preferowanego środka transportu, odległości miejsca wypoczynku, formy bazy noclegowej oraz długości pobytu. Rodziny z małymi dziećmi częściej zwracają uwagę na zdrowotne aspekty podróżowania. Jednak w porównywanych grupach tylko 1/3 badanych zasięga opinii lekarza przed wyjazdem. Rodzina to ważny segment współczesnego rynku turystycznego. Biura podróży powinny rozszerzać swoje oferty o charakterze rodzinnym. W ramach promocji zdrowia rodziny warto popularyzować prozdrowotną rolę aktywności turystycznej oraz kształtować zachowania zdrowotne związane z bezpiecznym podróżowaniem. Abstract Introduction. According to a family development theory, family environment evolves and each stage constitutes a phase in which a structure and functioning are different. It is reflected in healthy life style undertaken by a family. One of the forms of pro-health behaviours which transforms in ontogenesis and depends on current social and life conditions is physical activity. Tourism is an important kind of family’s physical activity. Aim. Therefore, the aim of this paper is to analyse preferences of tourist activity among young people with diversified family situation in the context of strengthening health potential of a family. Materials and methods. The research was carried out in year 2015, in a group of 200 women at the I and II stage of family ontogenesis. Methods of a diagnostic poll and authorial questionnaire were used. In statistical analysis chi-square test and Fisher’s Exact Test were applied. Results and conclusions. The examined families form I and II stage of ontogenesis differ with respect to frequency of travelling (p<0.01), choice of surroundings during holiday travels (p<0.05) and preferred boarding (p<0.01). Similarities are noticed in preferred transport, distance, accommodation and duration of holidays. Families with young children more often pay attention to health aspects of travelling. However, only one third of the respondents consult a doctor prior to journey. Family is an essential element of a contemporary tourist market. Travel agencies should expand their family offers. It is worth popularising pro-health role of tourist activity within family health promotion, as well as shaping health behaviours related to safe travelling. Słowa kluczowe: zdrowy styl życia, ontogeneza, cykl życia rodziny, aktywność turystyczna Key words: healthy life style, ontogenesis, family life cycle, tourist activity